Perbedaan Hasil Belajar Antara Siswa Yang Diajar Dengan Menggunakan Media Audio Dan Media Audio-Visual Pada Kelas V Di SD Negeri 58 Kota Bengkulu - Kurniawan, Dondi; Asiyah, Asiyah; Topano, Adrian (Yayasan Darussalam Bengkulu, 2022)
There have been many who have conducted research with the theme of Audio-Visual media and Audia Media, but there is no research on the differences in the use of these two media on student learning outcomes in science subjects. This study aims to determine differences in student learning outcomes between classes taught using audio media and audio-visual media in grade V at SD Negeri 58 Bengkulu City. This study used 2 groups, namely the VA class totaling 22 people as the experimental group and VB with 22 people as the control group. The research variable consisted of independent variables, namely audio-visual media with audio media, while the dependent variable was student learning outcomes. This type of research is quantitative. Data collection techniques are observation, documentation and multiple choice test questions. The data analysis technique used T-test. It can be seen from the results of the hypothesis using the